Peningkatkan Kemampuan Perkembangan Motorik Halus Melalui Kegiatan Mewarnai Gambar pada Anak Kelompok B TK Negeri Pembina Wonosegoro Boyolali - Wijiyanti Wijiyanti (JIM: Jurnal Ilmiah Mahasiswa Pendidikan Sejarah, 2023)
This study aims to develop children's fine motor skills through coloring pictures at the state kindergarten Pembina Wonosegoro Boyolali. This research is a classroom action research. The research subjects were 20 children from the kindergarten. The research was carried out for 2 cycles, cycle 1 was carried out on 16, 17 and 18 September 2019, cycle 2 was carried out on 23, 24 and 25 September 2019. Data collection was carried out by observation and interviews. The analysis technique uses a comparative method, namely comparing success between cycles. Developing children's fine motor skills through coloring pictures in the kindergarten averaged 43.54%, obtained 14 children. while 16 children had not yet completed, so there were 56.46% undeveloped children, 43.54% started to develop, developed according to expectations: 0% and developed rapidly: 0%. In cycle 1 the target of achieving completeness is expected to reach 60% after conducting research, it is obtained 59.48% with the criteria of children not yet developing: 0%, children starting to develop: 59.48%, children developing according to expectations: 40.52% and children developing very rapidly: 0%. Furthermore, in cycle 2 the researcher targeted 80% completeness, with continuous guidance and good cooperation from parents and students, then 30 students had achieved completeness with an average of 83.65% with undeveloped details: 0%, starting to develop: 0%, growing as expected: 83.65% and growing very rapidly: 16.35%.